PENERAPAN MODEL PROBLEM BASED LEARNING BERBASIS LITERASI SAINS UNTUK MENINGKATKAN PEMAHAMAN KONDISI GEOGRAFIS INDONESIA KELAS 5 SD - Yulianti Farida; Lilik Sri Hariani; Dwi Ma`rifatika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Science learning on the topic of Indonesia's geographical conditions in elementary schools still faces problems, including teacher-centered learning, low student engagement, limited conceptual understanding, and low science literacy. This study aimed to describe the implementation of the Problem-Based Learning (PBL) model based on science literacy and to improve fifth-grade students' understanding of Indonesia's geographical conditions. This study employed Classroom Action Research conducted in two cycles, each consisting of planning, action, observation, evaluation, and reflection. The subjects were 17 fifth-grade students of SDN Gadang 2 Malang in the 2025/2026 academic year. Data were collected through written tests and observation sheets, then analyzed descriptively using the average score and classical mastery percentage. The results showed that the implementation of PBL based on science literacy improved students' understanding of Indonesia's geographical conditions. The average score increased from 74.6 in Cycle I to 92.5 in Cycle II, while classical mastery increased from 82.4% to 100%. The learning process also encouraged students to actively analyze contextual problems, explain geographical phenomena scientifically, and relate learning concepts to everyday life. Thus, the application of the Problem-Based Learning model based on science literacy can be an effective alternative for improving students' conceptual understanding and science literacy in IPAS learning at the elementary school level.